A PYTHON CODE FOR GENERATING ALL PROPER SUBGROUPS OF DIHEDRAL GROUP - Syarifudin, Abdul Gazir; Wijaya, Verrel Rievaldo (Diponegoro University, 2023)
The dihedral group of order 2n denoted by D_2n is the symmetry group of a regular -polygon consisting of rotation and reflection elements and the composition of both elements. Like any other group, the dihedral group also have a subgroup whose numbers differs depending on the value of n. This research is conducted by studying past literature and explore a new development to a theory. In this paper, all the form of proper subgroups of D_2n will be given and all of these proper subgroups of D_2n will be generated and counted with the help of Python program.